Tourism and Development: A recent phenomenon built on old (institutional) roots? - Francesco Pigliaru; Adriana Di Liberto; Rinaldo Brau (European Regional Science Association (ERSA), 2010)
Is tourism an opportunity for lagging countries in the elusive quest for growth (Easterly, 2002)? Recent empirical evidence suggests that the answer is a cautious yes. Aggregate cross-country data show that tourism specialization is likely to be associated with higher per capita GDP growth rates than those observed in industrialized countries. However, this evidence ignores the importance of institutional quality and results are likely to be biased by omitted variable problems. In this paper we frame our starting question within the general debate about the importance of good/bad institutions as fundamental determinants of economic growth (Acemoglu et al., 2001) and ask whether previous positive results of tourism on growth are in fact driven by the presence of growth enhancing institutions. Our empirical analysis exploits newly available datasets and controls the robustness of previous results on growth and tourism in the presence of several institutional quality variables. By means of descriptive statistics and some simple cross-country regressions we confirm that the quality of institutions is important for growth. Yet our results strongly suggest that the weight of tourism in an economy is an independent and robust predictor of higher-than-average growth.
Keywords: O11; O50; O47; F43; L83; 330; Economic Development; Tourism Specialization; Institutions